2008
DOI: 10.3103/s1066530708040066
|View full text |Cite
|
Sign up to set email alerts
|

Models with a Kronecker product covariance structure: Estimation and testing

Abstract: In this article we consider a pq-dimensional random vector x distributed normally with mean vector θ and the covariance matrix Λ, assumed to be positive definite. On the basis of N independent observations on the random vector x, we wish to estimate parameters and test the hypothesis H: Λ = Ψ ⊗Σ, where Ψ = (ψ ij ) : q × q and Σ = (σ ij ) : p × p, and Λ = (ψ ij Σ), the Kronecker product of Ψ and Σ. That is instead of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
106
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 108 publications
(107 citation statements)
references
References 16 publications
(22 reference statements)
1
106
0
Order By: Relevance
“…From the likelihood function, constructed of independent observation matrices, Srivastava et al (2008) proved that the maximum likelihood estimates under the restriction ψ qq = 1, where Ψ = (ψ ij ) : q × q are found by an iterative flip-flop algorithm. Srivastava et al (2008) also showed that the likelihood equations provide unique estimators. A similar algorithm has been suggested by Mardia and Goodall (1993);Dutilleul (1999);Brown et al (2001) but without the restriction ψ qq = 1.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…From the likelihood function, constructed of independent observation matrices, Srivastava et al (2008) proved that the maximum likelihood estimates under the restriction ψ qq = 1, where Ψ = (ψ ij ) : q × q are found by an iterative flip-flop algorithm. Srivastava et al (2008) also showed that the likelihood equations provide unique estimators. A similar algorithm has been suggested by Mardia and Goodall (1993);Dutilleul (1999);Brown et al (2001) but without the restriction ψ qq = 1.…”
Section: Introductionmentioning
confidence: 99%
“…Srivastava et al (2008) discussed estimability of the paramters under the separability assumption. From the likelihood function, constructed of independent observation matrices, Srivastava et al (2008) proved that the maximum likelihood estimates under the restriction ψ qq = 1, where Ψ = (ψ ij ) : q × q are found by an iterative flip-flop algorithm. Srivastava et al (2008) also showed that the likelihood equations provide unique estimators.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations